A method to construct the dynamic landscape of a bio-membrane with experiment and simulation - Albert A. Smith; Alexander Vogel; Oskar Engberg; Peter W. Hildebrand; Daniel Huster (Nature Communications, 2022)
The authors present a strategy to construct dynamic biomolecular landscapes. Here, they derive a quantitative description of the distribution timescales and amplitudes of reorientational motion of POPC membranes from the combination of NMR relaxation data and frame analysis of MD simulations.